Pendampingan Penyusunan Modul Ajar Kurikulum Merdeka bagi MGMP Bahasa Indonesia Madrasah Aliyah di Kabupaten Demak - Chamalah, Evi; Azizah, Aida; Arsanti, Meilan; Setiana, Leli Nisfi; Wardani, Oktarina Puspita; Turahmat, Turahmat (IKIP PGRI Bojonegoro, 2024)
ABSTRACTCurriculum changes are a challenge felt by all educational institutions, especially Madrasah Aliyah (MA). The Independent Curriculum gives teachers the freedom to develop teaching tools, both in the form of Learning Implementation Plans (RPP) and teaching modules. However, the complexity of teaching modules, which are sometimes more detailed than lesson plans, often becomes an obstacle for teachers in designing learning tools. This obstacle is especially felt by Indonesian language teachers who are members of the Indonesian Language Subject Teacher Conference (MGMP). Some of the problems that arise include: (1) lack of knowledge regarding the preparation of Indonesian language teaching modules in MA in the context of the Independent Curriculum; (2) Indonesian Language MGMP MA Demak Regency has never participated in mentoring activities related to the preparation of Indonesian Language teaching modules in the Independent Curriculum; (3) the unavailability of Indonesian language teaching modules in MA according to the needs and characteristics of the school. To overcome this problem, several solutions are proposed, namely: (1) organizing mentoring activities regarding the preparation of Indonesian language teaching modules for the Indonesian Language MGMP Independent Curriculum MA Demak Regency; (2) implementation of learning and training activities related to the preparation of Indonesian language teaching modules for the Indonesian Language Independent Curriculum MGMP MA Demak Regency; (3) preparation of Indonesian language teaching modules in the Independent Curriculum MA in accordance with the needs and characteristics of the school.Keywords: mentoring, preparation of teaching modules, independent curriculum ABSTRAKPerubahan kurikulum menjadi suatu tantangan yang dirasakan oleh seluruh lembaga pendidikan, khususnya Madrasah Aliyah (MA). Kurikulum Merdeka memberikan kebebasan kepada guru untuk menyusun perangkat ajar, baik berupa Rencana Pelaksanaan Pembelajaran (RPP) maupun modul ajar. Namun, kompleksitas modul ajar, yang kadang lebih rinci daripada RPP, sering menjadi hambatan bagi guru dalam merancang perangkat pembelajaran. Kendala ini khususnya dirasakan oleh guru Bahasa Indonesia yang tergabung dalam Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Indonesia. Beberapa permasalahan yang muncul antara lain: (1) minimnya pengetahuan tentang penyusunan modul ajar Bahasa Indonesia di MA dalam konteks Kurikulum Merdeka; (2) MGMP Bahasa Indonesia MA Kabupaten Demak belum pernah mengikuti kegiatan pendampingan terkait penyusunan modul ajar Bahasa Indonesia pada Kurikulum Merdeka; (3) belum tersedianya modul ajar Bahasa Indonesia di MA sesuai dengan kebutuhan dan karakteristik sekolah. Untuk mengatasi permasalahan tersebut, beberapa solusi diajukan, yakni: (1) penyelenggaraan kegiatan pendampingan tentang penyusunan modul ajar Bahasa Indonesia pada Kurikulum Merdeka untuk MGMP Bahasa Indonesia MA Kabupaten Demak; (2) pelaksanaan kegiatan pembelajaran dan pelatihan terkait penyusunan modul ajar Bahasa Indonesia Kurikulum Merdeka untuk MGMP Bahasa Indonesia MA Kabupaten Demak; (3) penyusunan modul ajar Bahasa Indonesia di MA pada Kurikulum Merdeka yang sesuai dengan kebutuhan dan karakteristik sekolah.Kata Kunci: pendampingan, penyusunan modul ajar, kurikulum merdeka